The Outcasts: The Start of 'New Entertainment' in Pro-Regime Filmmaking in the Islamic Republic of Iran. Issue 1 (2nd January 2017) - Bajoghli, Narges
Abstract: With developments in the past decade of such popular films as Masoud Dehnamaki's trilogy, Ekhrajiha (The Outcasts), we are privy to a new trend in pro-regime filmmaking in Iran, one that centers on the creation of 'new entertainment.' This pivot by pro-regime cultural producers is based on a perceived need to do away with the 'war time propaganda' that 'no one wants to see anymore' (as one pro-regime screenwriter told me), and to replace it with 'new entertainment' that can engage with youth. The former head of Ansar-e Hezbollah in Iran, Masoud Dehnamaki, emerged at the forefront of this new movement by creating popular films that employ slapstick comedy about the war and which sell at historic box office numbers. His first narrative film, The Outcasts, is the focus of this article, as it signaled the beginning of a 'new entertainment' by pro-regime cultural producers. Based on ethnographic fieldwork, this article analyzes the film and filmmaker most responsible for the creation of 'new entertainment.'